2007
DOI: 10.1097/bot.0b013e318126bb56
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Avascular Necrosis of the Femoral Head by Measuring Intramedullary Oxygen Tension After Femoral Neck Fracture

Abstract: We believe that this method of measuring intramedullary oxygen tension is simpler and less invasive than other currently used methods and has the possibility for intraoperatively identifying a risk group that can develop a late segmental collapse of the femoral head secondary to avascular necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…By relating an extensive body of literature regarding the role of hypoxia in the solid tumor setting to what is currently known about the kinetics of MM disease progression, we have formed a hypothetical model of the role of hypoxia in MM disease progression (Figure 2). In the initial stages of disease establishment, we postulate that the hypoxic BM microenvironment [108][109][110]112 supports the initial survival and growth of the MM cells. 136 As the MM PCs establish themselves within the endosteal niche of the BM, they become exposed to even greater levels of hypoxia, 137 which activates HIF-1 and/or HIF-2, and stimulates the production of angiogenic factors and angiogenesis to increase oxygen delivery to the tumor cells, thereby facilitating tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…By relating an extensive body of literature regarding the role of hypoxia in the solid tumor setting to what is currently known about the kinetics of MM disease progression, we have formed a hypothetical model of the role of hypoxia in MM disease progression (Figure 2). In the initial stages of disease establishment, we postulate that the hypoxic BM microenvironment [108][109][110]112 supports the initial survival and growth of the MM cells. 136 As the MM PCs establish themselves within the endosteal niche of the BM, they become exposed to even greater levels of hypoxia, 137 which activates HIF-1 and/or HIF-2, and stimulates the production of angiogenic factors and angiogenesis to increase oxygen delivery to the tumor cells, thereby facilitating tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a prominent feature of the tumor microenvironment and considered an adverse prognostic factor best documented for solid tumors [9]. Hypoxia is also a physiological characteristic of the BM [10] and, as shown in mice studies, extremely hypoxic niches are essential for regulating the maintenance and functioning of hematopoietic stem cells [11], [12]. Several recent studies have demonstrated that MM displays features of hypoxia; in the 5T33M mouse MM model, myelomatous BM has been shown to be more hypoxic than normal BM.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other authors have suggested that invasive techniques, including arteriography, 29 , venography, 30,31 needle aspiration, 32 manometry, 33 oxymetry, 34,35 and measurement of intraosseous and intracapsular pressure, 36 are more sensitive and, therefore, possibly more appropriate diagnostic tools in the detection of vascularity of the femoral head. However, Calandruccio and Anderson 21 have suggested that, based on the accuracy of assessments of vascularity of the femoral head using these techniques, they are not sufficiently quantitative.…”
Section: Discussionmentioning
confidence: 78%